2020
DOI: 10.1111/cwe.12312
|View full text |Cite
|
Sign up to set email alerts
|

Digital Financial Inclusion and Consumption Smoothing in China

Abstract: In this paper, we investigate the effect of digital financial inclusion (DFI) on household consumption smoothing in China. We use four waves of the biennial China Family Panel Studies from 2010 to 2016, during which time DFI has significantly developed alongside financial technology across China. We split household income shocks into permanent and transitory components, and evaluate if DFI may help households to buffer against these shocks. We find that households are not able to insure against permanent shock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 25 publications
0
51
0
Order By: Relevance
“…A platform provided by digital finance facilitates increases in financial transactions, which subsequently generates higher tax revenue, benefiting governments that can then exert direct influence by orienting their activities [13,14]. Digital financial inclusion has diminished households' ability to insure against transitory income shocks, partly because the online purchase may lead to the oversensitivity of consumption to income [15]. Through investigation, Kemal found that digital payment enables female beneficiaries to receive social cash securely and conveniently [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A platform provided by digital finance facilitates increases in financial transactions, which subsequently generates higher tax revenue, benefiting governments that can then exert direct influence by orienting their activities [13,14]. Digital financial inclusion has diminished households' ability to insure against transitory income shocks, partly because the online purchase may lead to the oversensitivity of consumption to income [15]. Through investigation, Kemal found that digital payment enables female beneficiaries to receive social cash securely and conveniently [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e core data used in this study are the "Peking University Digital Financial Inclusion Index of China," which is compiled on the basis of hundreds of millions of microdata from a representative digital financial institution in China; this dataset reflects the cross-section and cross-time changes in the acquisition and use of digital financial services in China [31]. e index covers 31 provinces, 337 prefecture-level cities (regions, autonomous prefectures, and leagues collectively referred to as "cities"), and nearly 2,800 counties (county-level cities, banners, and municipal districts collectively referred to as "counties").…”
Section: Data Sourcesmentioning
confidence: 99%
“…Digital finance is a new financial format that relies on the Internet and information technology tools to carry out financial services and benefit more groups [ 18 , 20 , 24 , 25 ]. In essence, it is an important type and application of Financial Technology (FinTech) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%